KAJIAN PENANGANAN TERHADAP ANAK BERKEBUTUHAN KHUSUS - Purba Bagus Sunarya; Irvan, Muchamad; Dewi, Dian Puspa (LPPM Universitas PGRI Adi Buana Surabaya, 2018)
Children with special needs are children with disabilities or physical, mental, intellectual, social, or emotional barriers, such as: children with autism, deaf, blind, mental retradation, physical disability and others can have a significant effect on the process of growth or development compared to other children of his age. The problem of children with special needs is a problem that is quite complex in quantity and quality. This condition if not handled properly, the development of the child's ability to experience obstacles and the burden of parents, family, community and country.The purpose of handling done by all experts will have a positive impact for children with special needs. In various aspects such as in the field of academics able to follow the subjects well, in the social field of children able to socialize with the community and in the field of emotion children can channel emotions into positive things. Parents or families as primary service providers to children with special needs, generally still lack the awareness and responsibility to provide equal rights and opportunities for the children. This is because the lack of knowledge of parents or families about how to care for, educate, nurture and meet the needs of these children. Parents or families are the most important factor in facilitating the growth and protection of children with special needs